Hubungan Nilai MPV (Mean Platelet Volume) dengan Kadar Glukosa Darah pada Penderita Diabetes Melitus Tipe 2: The Correlation Of MPV (Mean Platelet Volume) Value with Blood Glucose Levels in Patients of Diabetes Mellitus Type 2 - Hari Saktiningsih; Mastuti Widi Lestari; Warih Anjari Dyah Kusumaning Ayu (Jurnal Surya Medika (JSM), 2022)
Diabetes mellitus (DM) type 2 is a group of disorders characterized by elevated blood glucose levels (hyperglycemia). This condition is caused by a decrease in the body's ability to respond to insulin (insulin resistance) or due to a decrease in the amount of insulin by the pancreas. Mean platelet volume (MPV) indicates platelets' mean size and activity. In diabetics, a high MPV value can predict an increased risk of thrombosis and chronic complications. This study aimed to determine the relationship between MPV values and blood glucose in Type 2 DM. The type of this research was observational analytic with a cross-sectional design; the respondents were type II diabetes mellitus patients at the Gajahan Health Center Surakarta from May to July 2018. The results of the Spearman test obtained p = 0.082 so that p > (0.05), then H0 is accepted and H1 is rejected so that it can be concluded that there is no relationship between MPV values and Blood Glucose Levels in patients with type II diabetes mellitus.